ANALISIS DIGITALISASI PEMBELAJARAN SEKOLAH DASAR WILAYAH PERBATASAN - Purnasari, Pebria Dheni; Damas Sadewo, Yosua; Samuel Slamet Santosa, Donald; Sanoto, Herry (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2024)
The use of digitalization has spread to all levels of society, regardless of social status. This requires the education field to be responsive and able to consistently integrate digitalization into the learning process, so that students are accustomed and develop their competencies. However, unfortunately there are still many schools having difficulty in implementing the integration of digitalization into the learning process, as well as a study of science and media. Some of the schools are not even aware whether they are ready to implement the digitalization into differentiated learning..Therefore, to prepare for the digitalization of learning, it is necessary to first analyze how prepared the school is to welcome this era of digitalization. Thus, the purpose of this study is to analyze the readiness level of digitalization of elementary schools specifically to be carried out in the Bengkayang region, West Kalimantan. The research method used was the descriptive method. The data collection was carried out using a digitalization level measurement instrument, namely as a limited-scale trial stage. Apart from that, unstructured interviews and observations were also carried out to strengthen the data collected. The number of schools that were respondents were 10 elementary schools in Bengkayang. The research results show that 80% of schools are categorized as ‘not ready’, while only 20% are ready to implement differentiated learning. The assessment results from education reports also show the similar condition.